Desistance from crime and identity: an empirical test with survival time - Paternoster, Raymond (Criminal justice and behavior, 2016)
Theories of desistance from crime have emphasized social processes like involvement in adult social bonds or prosocial social relationships to the deliberate neglect of individual subjective processes such as one?s identity. More recent theories, however, have stressed the role of identity and human agency in the desistance process. An important set of questions is whether identity theory adds anything to existing theories, and whether there is empirical evidence to suggest that such subjective processes are important. In this article, we provide an empirical assessment of individual subjective considerations in desistance by looking at the relationship between ?good identities,? intentional self-change, and desistance using survival time data from a sample of serious drug-troubled adult offenders released from prison whose arrest records are followed for almost a 20-year period. The implications of our findings for all brands of criminal desistance theory are discussed.